Numerical Analysis of the Effect of Opening Shape and Spacing on the Damping Ratio of Castellated Beams - Fayza Aughitri; Guntur Nugroho (UIN Sunan Gunung Djati Bandung, 2026)
Castellated beams are widely applied in modern steel structures due to their lightweight characteristics and high stiffness. While most previous studies have focused on natural frequency and stiffness behavior, limited attention has been given to the damping performance of castellated beams with different web-opening geometries. This study investigates the effect of opening shape and spacing on the damping ratio (ζ) of IWF steel castellated beams using finite element simulations in Abaqus. The damping ratio was derived from the free-vibration decay curve using the logarithmic decrement method, which allows the damping value to be determined accurately from the curve data. This method is particularly suitable for steel structures, as steel typically has low damping. Results indicate that the solid beam exhibits a baseline damping ratio of 3.3%, while circular openings maintain relatively stable damping values between 2.9–3.1%. In contrast, square openings reduce ζ more significantly, reaching values as low as 2.6%. This study suggests adopting circular web openings in castellated steel beams, as this configuration demonstrates superior structural performance and yields response values closer to those of solid steel than square openings. These findings highlight that opening geometry and spacing significantly affect the dissipation of vibration energy in castellated beams. The outcomes provide useful insights for designing vibration-sensitive steel structures, particularly for long-span applications.